Evaluation of healing of periapical tissue in permanent incisors with open apices after unintentional extrusion of mineral trioxide aggregate - A retrospective study - Sonali Roy; Archana Kumari; Praveen Chandra; Ritika Agarwal; Pinki Bankoti; Farah Ahmed (Wolters Kluwer Medknow Publications, 2021)
Aim: The aim of the present study was to retrospectively assess the healing of periapical lesions in permanent central incisors with open apices after unintentional extrusion of mineral trioxide aggregate (MTA). Materials and Methods: The clinical and radiographic records of 75 maxillary permanent central teeth treated by MTA apexification were evaluated. Teeth with unintentionally extruded MTA formed the study group (Group 1, n = 28), whereas the teeth with no MTA extrusion formed the control group (Group 2, n = 47). For both the groups, the records were analyzed for a follow-up period of 3 years. Results: Complete healing (CH) was observed in 25 teeth in the study group, whereas all the teeth in the control group showed CH (P > 0.05). Within the study group, 6 teeth (21%) showed CH in the 6th month in Group 1, whereas in the control group, 34 teeth (72.3%) showed CH (P < 0.001). At the 1-year follow-up appointment, 19 teeth (67.8%) showed CH in Group 1, whereas 9 teeth (19.1%) showed the same result in Group 2 (P < 0.001). At the end of the 3-year follow-up period, it was noticed that in 21 (84%) teeth, extruded MTA remained unchanged, whereas it was reduced in 4 (16%) of them (P < 0.001). Conclusion: Extrusion of MTA does not have a significant effect on the healing of the periapical lesion. However, it may lead to a delay in the healing of periapical healing. Patients should be informed about the complication and consequences of extruded MTA and should be kept on follow-up to observe periapical healing.